2011
DOI: 10.1111/j.1471-0528.2011.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, frequency and problem rating of hot flushes persist in older postmenopausal women: impact of age, body mass index, hysterectomy, hormone therapy use, lifestyle and mood in a cross‐sectional cohort study of 10 418 British women aged 54–65

Abstract: Prevalence, frequency and problem rating of hot flushes persist in older postmenopausal women: impact of age, body mass index, hysterectomy, hormone therapy use, lifestyle and mood in a cross-sectional cohort study of 10 418 British women aged 54-65 Objective Hot flushes and night sweats (HFs/NSs) are the main menopausal symptoms, but few studies have been adequately powered to examine the dimensions or predictors of experiencing HFs/NSs. We report on these variables in a large UK cohort of postmenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 66 publications
5
84
0
Order By: Relevance
“…Women who have a hysterectomy with bilateral oophorectomy (both ovaries removed) are consistently reported to have a higher risk of more frequent and/or severe hot flushes and night sweats, which is thought to be related to the abrupt decline in oestrogen levels post-surgery [5]. For women who have a hysterectomy with ovarian conservation (one or both ovaries retained) the reported associations are less consistent [6][7][8]. The proportion of women who retain one or both ovaries at the time of hysterectomy varies by country, ranging from 46% to 82% [4], highlighting the need to increase our understanding of the symptom experiences of these women.…”
Section: Introductionmentioning
confidence: 67%
“…Women who have a hysterectomy with bilateral oophorectomy (both ovaries removed) are consistently reported to have a higher risk of more frequent and/or severe hot flushes and night sweats, which is thought to be related to the abrupt decline in oestrogen levels post-surgery [5]. For women who have a hysterectomy with ovarian conservation (one or both ovaries retained) the reported associations are less consistent [6][7][8]. The proportion of women who retain one or both ovaries at the time of hysterectomy varies by country, ranging from 46% to 82% [4], highlighting the need to increase our understanding of the symptom experiences of these women.…”
Section: Introductionmentioning
confidence: 67%
“…In line with these results, Barnabei et al (2002) analysed data from the Heart and Estrogen/Progestin Replacement Study and found that almost 20% of women aged 70-74 years reported very frequent or frequent hot flushes [6] while Rödström et al (2002) reported a lower number, that only 9% of the 72-year old women were troubled by hot flushes [7]. A recent large cohort study [8] on 202638 postmenopausal women showed that menopausal symptoms were still present in 54% 10 years after menopause and that the symptoms and their frequency remained constant from 55 to 65 years of age. The authors concluded that previous studies may have underestimated the duration of menopausal symptoms.…”
Section: Introductionmentioning
confidence: 69%
“…There are over 3.5 million women in employment aged between 50 and 65 in the UK [1] and, as menopause occurs on average between the ages of 50-51 and can last for up to ten years [2] at any one time, a significant proportion of mid-aged and older women workers will be experiencing menopausal symptoms. Hot flushes and night sweats (HFNS) are the main symptoms of the menopause, which for an estimated 20-25% affect quality of life (QOL) largely due to discomfort, embarrassment and the impact of night sweats upon sleep [3,4].…”
Section: Introductionmentioning
confidence: 99%